2009
DOI: 10.3168/jds.2008-1432
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of molasses and monensin in alfalfa hay- or corn silage-based diets on rumen fermentation, total tract digestibility, and milk production by Holstein cows

Abstract: Sugar supplementation can stimulate rumen microbial growth and possibly fiber digestibility; however, excess ruminal carbohydrate availability relative to rumen-degradable protein (RDP) can promote energy spilling by microbes, decrease rumen pH, or depress fiber digestibility. Both RDP supply and rumen pH might be altered by forage source and monensin. Therefore, the objective of this study was to evaluate interactions of a sugar source (molasses) with monensin and 2 forage sources on rumen fermentation, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
1
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 51 publications
(108 reference statements)
12
79
1
12
Order By: Relevance
“…Alfalfa hay as a sole source of forage in diets may alleviate effects of dietary treatments on rumen condition and rapid fermentation by inhibiting lactic acid producing bacteria and there by sustaining stable rumen environment. Oelker et al [28] observed that any changes in rumen pH with alfalfa hay relative to corn silage based diets decreased the accumulation of biohydrogenation intermediates and thereby total CLA content in rumen of Holstein dairy cows. Rumen microbial enzymes are responsible for the isomerisation and hydrolysis of dietary lipid and the conversion of unsaturated fatty acids to various partially and fully saturated derivatives, including CLA (C18:2 cis-9, t-11) (c), trans vaccenic acid (C18:1 t-11) (VA) and stearic acid (C18:0).…”
Section: Diet and Milk Conjugated Linoleic Acid (Cla) Contentsmentioning
confidence: 99%
“…Alfalfa hay as a sole source of forage in diets may alleviate effects of dietary treatments on rumen condition and rapid fermentation by inhibiting lactic acid producing bacteria and there by sustaining stable rumen environment. Oelker et al [28] observed that any changes in rumen pH with alfalfa hay relative to corn silage based diets decreased the accumulation of biohydrogenation intermediates and thereby total CLA content in rumen of Holstein dairy cows. Rumen microbial enzymes are responsible for the isomerisation and hydrolysis of dietary lipid and the conversion of unsaturated fatty acids to various partially and fully saturated derivatives, including CLA (C18:2 cis-9, t-11) (c), trans vaccenic acid (C18:1 t-11) (VA) and stearic acid (C18:0).…”
Section: Diet and Milk Conjugated Linoleic Acid (Cla) Contentsmentioning
confidence: 99%
“…This pH was in the range (6.5-7.0) of ideal condition for microbial activities in the rumen for fiber and protein digestion (Wanapat & Cherdthong 2009;Calabro et al 2008). Oelker et al (2009) also reported similar ruminal pH of cows fed on corn silage or chopped alfalfa hay. Rumen ammonia (NH3-N) was significantly higher in grass basal diet than the CCS diet.…”
Section: Resultsmentioning
confidence: 57%
“…The propionate concentration was not different between the NDCP and HDCP treatments, and does not provide an explanation for the decrease in milk yield when maize was replaced with DCP. Increased levels of sugar in the diet have been shown to decrease the acetate concentration (Khalili & Huhtanen, 1991;Chamberlain et al, 1993;Broderick et al, 2008), increase butyrate concentration (Khalili & Huhtanen, 1991, Chamberlain et al, 1993 and result in no change in acetate concentration or the acetate: propionate ratio (Khalili & Huhtanen, 1991;Leiva et al, 2000;Oelker et al, 2009). In theory, the replacement of maize with DCP should lead to a change in the VFA profile of the rumen.…”
Section: Discussionmentioning
confidence: 99%